2006
DOI: 10.1021/jo060976f
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Approaches for the Synthesis of the Antitumoral Peptide, Kahalalide F. Study of Orthogonal Protecting Groups

Abstract: Kahalalide compounds are peptides that are isolated from a Hawaiian herbivorous marine species of mollusc, Elysia rufescens, and its diet, the green alga Bryopsis sp. Kahalalide F and its synthetic analogues are the most promising compounds of the Kahalalide family because they show anti-tumoral activity. Linear solidphase syntheses of Kahalalide F have been reported. Here we describe several new improved synthetic routes based on convergent approaches with distinct orthogonal protection schemes for the prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
0
32
0
2
Order By: Relevance
“…The last amino acid, Fmoc-(2 S ,3 S )-Ile, was coupled onto the unprotected alcohol using 5 equiv of Fmoc-(2 S ,3 S )-Ile, 5 equiv of DIC, 0.25 equiv of DMAP (4-dimethylaminopyridine), and 1 equiv of DIPEA ( N , N -diisopropylethylamine) in DMF for 45 min twice. 44 In order to prevent nucleophilic displacement of the ester bond by piperidine, the Fmoc group of this amino acid was instead removed using the non-nucleophilic base DBU (5% v/v in DMF, RT, 5 min).…”
Section: Resultsmentioning
confidence: 99%
“…The last amino acid, Fmoc-(2 S ,3 S )-Ile, was coupled onto the unprotected alcohol using 5 equiv of Fmoc-(2 S ,3 S )-Ile, 5 equiv of DIC, 0.25 equiv of DMAP (4-dimethylaminopyridine), and 1 equiv of DIPEA ( N , N -diisopropylethylamine) in DMF for 45 min twice. 44 In order to prevent nucleophilic displacement of the ester bond by piperidine, the Fmoc group of this amino acid was instead removed using the non-nucleophilic base DBU (5% v/v in DMF, RT, 5 min).…”
Section: Resultsmentioning
confidence: 99%
“…This peptide acts on the liposome membrane of tumor cells and modifies its basal function (Figure 1) (Hamann et al, 1996; Singh et al, 2008). Moreover, it modifies the role of the lysosomal membrane, leading to intracellular acidification and cell death, a characteristic that discriminates it from all other known antitumor agents (Gracia et al, 2006). This peptide also appears to inhibit the expression of certain specific genes that are involved in DNA replication and cell proliferation, thereby inhibiting tumor spreading and growth.…”
Section: Introductionmentioning
confidence: 99%
“…11 Since the quantities of the natural product available were inadequate for future additional clinical studies convergent strategies for solid phase synthetic routes were developed. 12 As a part of our structure-activity relationship studies of 1 and isoKF analogs, we have recently reported the first solution phase semi-synthetic modification and lead optimization of 1 that can be adapted to a drug generated through fermentation. 13 …”
Section: Introductionmentioning
confidence: 99%